Meningkatkan Minat dan Hasil Belajar Senam Irama dengan Media “Sekawat” Siswa SMP - Widiastuti, Sendang Sri (Jurnal Didaktika Pendidikan Dasar, 2022)
To achieve maximum learning outcomes, teachers must be able to apply various learning models and use appropriate learning media. This class action research in 2 cycles aims to determine the increase in student interest and learning outcomes in learning rhythmic gymnastics using Sekawat media for class VII D students of SMP Negeri 2 Pakem Special Region Yogyakarta SMP. Methods of data collection by observation, tests, questionnaires, documentation, and field notes. The data analysis used was descriptive qualitative to describe student interest and descriptive quantitative to describe student learning outcomes. The results showed that the use of Sekawat media can increase students’ interest in learning rhythmic gymnastics from 58% to 88% at the end of the action and can increase student learning outcomes from an average of 20% in the pre-cycle to 85.7% at the end of the action.